Peranan Penasehat Hukum dalam Menegakkan Hak dan Kewajiban Hukum Klien dalam Proses Peradilan Pidana serta Kendala-Kendala yang Dihadapi di Pengadilan Negeri Atambua Kabupaten Belu - Catharina De Ricci Yovita Febriani Kiik; Rudepel Petrus Leo; Adrianus Djara Dima (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to analyze the role of legal counsel in upholding the legal rights and obligations of clients in the criminal justice process as well as the obstacles faced in Atambua District Court, Belu Regency. The research method used in this research is Empirical research. The result of this research is that the role of Legal Counsel in upholding the rights and legal obligations of clients in the criminal justice process at the Atambua District Court of Belu Regency is to provide legal assistance, uphold the human rights of suspects or defendants in court. The obstacles faced by counsel in upholding the rights and legal obligations of clients are that the BAP made by investigators is often denied and denied its truth and legality. The effort of legal counsel in facing the obstacles of assisting suspects or defendants in the Atambua District Court of Belu Regency is to escort the case until the verdict at the court level.